2016
DOI: 10.1016/j.sapharm.2015.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Examining hospital pharmacists' goals for medication counseling within the communication accommodation theoretical framework

Abstract: Abstract AbstractBackground

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
(39 reference statements)
1
3
0
Order By: Relevance
“…In our earlier work, we obtained hospital pharmacists’ views about their roles and goals in medication counselling in focus groups and mapped these pharmacist‐identified goals to CAT strategies . Next, audio‐recorded hospital pharmacist–patient conversations were investigated by our group to determine how well pharmacists utilised CAT strategies in their exchanges with patients .…”
Section: Introductionmentioning
confidence: 99%
“…In our earlier work, we obtained hospital pharmacists’ views about their roles and goals in medication counselling in focus groups and mapped these pharmacist‐identified goals to CAT strategies . Next, audio‐recorded hospital pharmacist–patient conversations were investigated by our group to determine how well pharmacists utilised CAT strategies in their exchanges with patients .…”
Section: Introductionmentioning
confidence: 99%
“…However, the way that graduates. with less inclusive understandings of the meaning of patient-centredness, interact with patients/customers is consistent with the findings of many previous studies of pharmacists in a range of practice settings, internationally (Braaf et al, 2015;Cavaco & Romano, 2010;Chen & Britten, 2000;Chevalier et al, 2016aChevalier et al, , 2016bChevalier et al, , 2017Greenhill et al, 2011;Hargie, Morrow, & Woodman, 2000;Montgomery et al, 2010;Murad et al, 2014;Shah & Chewning, 2006van Dijk et al, 2016;Waring et al, 2016).…”
Section: The Meaning Of Patient-centredness In Pharmacy Practicesupporting
confidence: 89%
“…Thus there are gaps in patient involvement, empathy, reflective listening and eliciting the patient perspective and concerns (Cavaco & Romano, 2010;Chen & Britten, 2000;Greenhill, Anderson, Avery, & Pilnick, 2011;Guirguis, 2011;Montgomery et al, 2010;Murad et al, 2014;Shah & Chewning, 2006van Dijk et al, 2016;Waring, Latif, Boyd, Barber, & Elliott, 2016). Hospital pharmacists have reported that when under time pressures, they feel compelled to hastily provide routine information as a means to enhance efficiency (Braaf et al, 2015;Chevalier, Watson, Barras, & Cottrell, 2016a;Chevalier et al, 2016b). In a minority of these observational studies, pharmacists demonstrate what is deemed to be patient-centred communication in their practice, mainly in specialist clinics, for example HIV clinics (Chen & Britten, 2000;Murad et al, 2014;Watermeyer & Penn, 2009).…”
Section: Studying Pharmacy Practice and Developmentmentioning
confidence: 99%
“…The way that some graduates in this study, such as Annie, communicated with patients was not dissimilar to findings from previous studies reporting the use of closed questions and unilateral transmission of generalised information. [14][15][16][17][18][19][20][21][22][23][36][37][38] So, this way of being a pharmacist was not unique to some pharmacists in this study. However, as described above, other pharmacists understood and enacted patient-centredness more broadly to varying extents.…”
Section: Discussionmentioning
confidence: 99%